Characterization of capsid and noncapsid proteins of B19 parvovirus propagated in human erythroid bone marrow cell cultures. - Ozawa, K (1987)
The major capsid and noncapsid proteins of the pathogenic parvovirus B19, propagated in vitro, were detected by sodium dodecyl sulfate-polyacrylamide gel electrophoresis, immunoprecipitation, and immunoblot of the erythroid fraction of infected human bone marrow cell cultures. There were two capsid proteins of 58 kilodaltons (kDa; the major species) and 84 kDa (the minor species). Newly synthesized capsid viral proteins were present in the supernatants of infected cultures. The major noncapsid protein of 77 kDa was localized to the nucleus.